The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.14198/jhse.2018.132.15
|View full text |Cite
|
Sign up to set email alerts
|

The attentional focus impact on tennis skills’ technique in 10 and under years old players: Implications for real game situations

Abstract: The aim of the present study was to examine the effect of the internal and external focus of attention instructions on performance and learning of the service, forehand and backhand tennis skills at 8 -9 years old tennis players. 68 participants of 8 -9 years old (M=8.8, SD=0.54), were divided in three groups and followed a 6 weeks intervention program; the internal attentional focus group (N=21), the external attentional group (N=23) and the control group (N=24). Three measurements were implemented (pre, post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 23 publications
(25 reference statements)
1
14
0
Order By: Relevance
“…In order to combat this attentional lapse, teachers must try other strategies to expose the information and «guide» students' attention, as stated in Ladewig (2017) and Grube, Ryan, Lowell, and Stringer (2018). In addition, the feedback given by the teacher are equally important for better learning, so researchers like Wulf, Chiviacowsky, Schiller and Avila (2010), Wulf (2013), Kim, Jimenez-Diaz, and Chen (2017) and Tsetseli , Zetou, Vernadakis and Mountaki (2018), concluded that the feedbacks directed to an external focus show more benefits and development in completing the task or exercise, than the internally focused group.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to combat this attentional lapse, teachers must try other strategies to expose the information and «guide» students' attention, as stated in Ladewig (2017) and Grube, Ryan, Lowell, and Stringer (2018). In addition, the feedback given by the teacher are equally important for better learning, so researchers like Wulf, Chiviacowsky, Schiller and Avila (2010), Wulf (2013), Kim, Jimenez-Diaz, and Chen (2017) and Tsetseli , Zetou, Vernadakis and Mountaki (2018), concluded that the feedbacks directed to an external focus show more benefits and development in completing the task or exercise, than the internally focused group.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…In the specific case of attention, it's considered as an important mediating variable in the teaching/learning process, and therefore this variable has been studied by several researchers (Santos, Petrica, Serrano & Mesquita, 2014;Emad, Neumann & Abel, 2017;Kim, Jimenez-Diaz, & Chen, 2017;Navarro-Patón, Lake-Ballesteros, Basanta-Camino, & Arufe-Giraldez, 2018 ;Tsetseli, Zetou, Vernadakis, & Mountaki, 2018;. Petrica and Tavares (1999) studied students' attention of the 2nd cycle in physical education classes, using an observational method in which the results show that students are aware of the task and the instructions given by the teacher.…”
Section: Introductionmentioning
confidence: 99%
“…They argue that in studies with more stable (closed) environments, no differences were found between the internal and external attentional focus group, in movements such as golf shot (Wulf et al, 2003) and soccer kick from a fixed ball position (Uehara et al, 2008). This may lead to the conclusion that instructions directing the attention externally may be more effective and beneficial for open skills (Castaneda & Gray 2007;Tsetseli et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Attention has an important role in the teaching/learning process, as shown on investigations such as Petrica and Tavares (1999), Petrica (2003), Santos (2009), Santos et al, (2020) that measured and plotted attentional profiles during physical education classes. We also found studies with an emphasis on attentional focus, such as Tsetseli, Zetou, Vernadakis and Mountaki (2018) who studied the attentional focus of young people while practicing tennis. They found that students who received feedback from external nature had better results than students who received internal feedbacks.…”
Section: Introductionmentioning
confidence: 88%